Fms-Like tyrosine kinase-3 ligand attenuates local and systemic infection in a model of post-burn pneumonia - Hundeshagen, Gabriel; Cui, Weihua; Musgrove, Lindsay; Cherry, Aaron; Lee, Seung-Jin; Cox, Robert A.; Toliver-Kinsky, Tracy (Shock, 2018)
Background: - Burn injury induces immunosuppression and promotes infection with opportunistic pathogens. Pneumonia and sepsis are leading causes of post-burn morbidity and mortality. Fms-like tyrosine kinase-3 ligand (Flt3L) improves local and systemic resistance to P aeruginosa-associated burn wound infection. This study evaluates the effects of post-burn prophylactic Flt3L treatment on local and systemic infection and inflammation in a murine model of pneumonia and sepsis. - Methods: - Mice received a severe scald burn, were treated with Flt3L or vehicle (CTR) for 5 days, and inoculated trans-nasally with P aeruginosa. Lung, blood, and spleen were harvested at 24 and 48 h postinoculation (p.i.) to assess infection (bacterial burden, bacteremia, distant organ manifestation) and inflammation (interleukin-6 (IL-6) and myeloperoxidase (MPO) levels). Histology correlated infection and inflammation parameters with morphology. Survival at various bacterial concentrations was monitored for 14 days p.i. - Results: - Bacterial burden was significantly reduced in lung and spleen of Flt3L-treated mice. Flt3L treatment was associated with decreased signs of pulmonary inflammation (reduced wet weight and IL-6 levels), lower incidences of bacteremia and septic distant organ manifestation, and reduced systemic inflammation (IL-6 and MPO). Histologically, reduced alveolar and peribronchiolar neutrophil and lymphocyte infiltration indicated attenuated pulmonary inflammation after Flt3L treatment. Overall survival was comparable between groups for all doses of P aeruginosa, but mortality delayed in the Flt3L-treated group. - Conclusion: - Prophylactic treatment with Flt3L could augment antimicrobial therapy of post-burn pneumonia through improvement of the initial host response to challenge with P aeruginosa, attenuate local, and systemic inflammation as well as septic pathogen dissemination.
Gesehen am 30.04.2020